Strategies to reduce attrition in weight loss interventions: A systematic review and meta‐analysis. (26th July 2019) - Pirotta, Stephanie; Joham, Anju; Hochberg, Lisa; Moran, Lisa; Lim, Siew; Hindle, Annemarie; Brennan, Leah
Summary: The primary objective of the study was to identify the effect of intervention strategies on attrition within a weight loss programme among adults aged 18 to 65 years. The secondary objective of the study was to assess the impact of such intervention strategies among female‐only weight loss programmes. The literature search was performed in Ovid (CINAHL Plus, MEDLINE, EMBASE, Cochrane [Cochrane Database of Reviews, Cochrane Central Register of Controlled Trials, and Cochrane Methodology Register], and PsycINFO). Studies must have identified weight loss as the main aim and compared the primary weight loss programme alone (control) with the primary weight loss programme coupled with an additional intervention strategy (intervention). Papers must have had a mean participant age between 18 and 65 years and available in English. Fifty‐seven trials met the inclusion criteria and were included in the meta‐analysis. Strategies that successfully reduced attrition included the incorporation of financial incentives (n = 8), a multicomponent approach (n = 13), and use of self‐monitoring technology (n = 4). The majority of studies were of low to moderate methodological quality because of insufficient reporting. A limited number of female‐only trials were found (n = 13). Implementation of financial incentives, multicomponent interventions, and self‐monitoring technology help reduce attrition among adult weight loss programmes. Further studies are required to identify the impact of intervention strategies on attrition in women.